Development of Literacy and Numeracy E-Comic as An Independent Curriculum Learning Method For Primary School Teacher - Siagian, Anggi Rafialdi; Aisyah, Siti; Simamora, Sheila Septina; Nainggolan, Ayu Miranda; Nainggolan, Yuliana Mona Krisdiana (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
Literacy and numeracy e-comic is a type of digital comic designed to teach readers letters and numbers. It is beneficial for improving reading and counting skills as well as the ability to understand information through a more engaging and interactive medium. The purpose of this research is to study the potential of e-comics to improve literacy and numeracy as well as the benefits and problems associated with using them in formal and informal education. The study used literature and a qualitative approach. The results show that e-comics can serve as an effective and engaging learning tool to improve literacy and numeracy, both inside and outside the classroom. The emergence of various e-comics platforms also opens up new opportunities to improve literacy and numeracy through story customization, interactivity and user engagement.